Real-world utilization of molecular diagnostic testing and matched drug therapies in the treatment of metastatic cancers. (3rd June 2018) - Chawla, Anita; Peeples, Miranda; Li, Nanxin; Anhorn, Rachel; Ryan, Jason; Signorovitch, James
Abstract: Aims: To assess the frequency of biopsies and molecular diagnostic testing (human DNA/RNA analysis), anti-cancer drug use (genomically-matched targeted therapy [GMTT], unmatched targeted therapy [UTT], endocrine therapy [ET], and chemotherapy [CT]), and medical service costs among adults with metastatic cancer. Methods: Adults diagnosed with metastatic breast, non-small cell lung (NSCLC), colorectal, head and neck, ovarian, and uterine cancer (2010Q1–2015Q1) were identified in the OptumHealth Care Solutions claims database and followed from first metastatic diagnosis for ≥1 month and until the end of data availability. Utilization was assessed for each cancer cohort (all and patients aged ≥65 years); per-patient-per-month (PPPM) medical service costs were assessed for all patients. Testing frequency estimates were applied to Surveillance, Epidemiology, and End Results Program data to estimate the number of untested patients (2010–2014). Results: Patients with metastatic cancer ( n  = 8, 193; breast [ n  = 3, 414], NSCLC [ n  = 2, 231], colorectal [ n  = 1, 611], head and neck [ n  = 511], ovarian [ n  = 275], and uterine [ n  = 151]) were 63 years old (mean), with 11.1–22.2 months of observation. Biopsy and molecular diagnostic testing frequencies ranged from 7% (uterine) to 73% (ovarian), and from 34% (head and neck) to 52% (breast), respectively. Few were treated with GMTT (breast, 11%; NSCLC, 9%; colorectal, 6%). Treatment with UTT ranged from 0.7% (uterine) to 21% (colorectal). Biopsy, diagnostic testing, and anti-cancer drug therapy were less frequent for those ≥65 years. Medical service costs (PPPM, mean) ranged from $6, 618 (head and neck) to $9, 940 (ovarian). The estimated number of untested new patients with metastatic cancer was 636, 369 (all) and 341, 397 (≥65). Limitations: In addition to the limitations of claims analyses, diagnostic testing frequency may be under-estimated if patients underwent testing prior to study inclusion. Conclusions: The low frequency of molecular diagnostic testing suggests there are opportunities to better inform management of patients with advanced cancer, particularly decisions to treat with GMTT.